Efficacy of transoral outlet reduction in Roux-en-Y gastric bypass patients to promote weight loss: a systematic review and meta-analysis - Dhindsa, Banreet Singh; Saghir, Syed Mohsin; Naga, Yassin; Dhaliwal, Amaninder; Ramai, Dayl; Cross, Chad; Singh, Shailender; Bhat, Ishfaq; Adler, Douglas G. (Endoscopy International Open, 2020)
Background and study aims Transoral outlet reduction (TORe) is an endoscopic procedure used in patients with weight gain post Roux-en-Y gastric bypass (RYGB). We performed a systematic review and meta-analysis to evaluate the efficacy and safety of TORe with a full-thickness suturing device for treating patients with weight regain after RYGB.Patients and methods We conducted a comprehensive search of several databases and conference proceedings including PubMed, EMBASE, Google-Scholar, MEDLINE, SCOPUS, and Web of Science databases (earliest inception to March 2020). The primary outcomes assessed were technical success, absolute weight loss (AWL) and percent of total weight loss (% TWL) at 3, 6, and 12 months after the procedure. The secondary outcomes assessed were pooled rate of adverse events (AEs), adverse event subtypes and association of size of gastrojejunal anastomosis (GJA) and percent TWL.Results Thirteen studies on 850 patients were included. The pooled rate of technical success was 99.89 %. The absolute weight loss (kg) at 3, 6, and 12 months was 6.14, 10.15, and 7.14, respectively. The percent TWL at 3, 6, and 12 months was 6.69, 11.34, and 8.55, respectively. The pooled rate of AE was 11.4 % with abdominal pain being the most common adverse event. The correlation coefficient (r) was –0.11 between post TORe GJA size and weight loss at 12 months.Conclusion TORe is an endoscopic procedure that is safe and technically feasible for post RYGB with weight gain.